The American 1890s : a cultural reader - Smith, Susan Harris; Dawson, Melanie, 1967- (e-Duke books scholarly collection., 2000)
An anthology of articles from periodicals of the 1890s, chosen to reflect various aspects of American culture during the last fin-de-siecle.